Transition from Ambrisentan to Bosentan in Pulmonary Arterial Hypertension: A Single-Center Prospective Study - Su-Gang Gong; Lan Wang; Bigyan Pudasaini; Ping Yuan; Rong Jiang; Qin-Hua Zhao; Jing He; Rui Zhang; Wen-hui Wu; Jin-Ming Liu; Cai-cun Zhou (Canadian Respiratory Journal)
Background and objective: Two endothelin receptor antagonists (ETRAs), bosentan and ambrisentan, are approved for patients with pulmonary arterial hypertension (PAH). However, there is little information about the transition strategy between these two ETRAs. We aimed to evaluate the safety and efficacy from ambrisentan to bosentan. Methods: Twenty PAH patients were enrolled into the single-center, open-labelled prospective study. Echocardiogram, WHO functional class (WHO-FC), 6-minute walking distance (6MWD), right heart catheterization, and hemotology were collected. After receiving oral 5 mg ambrisentan daily initially for one year, the patients were divided into two arms: eight patients switched to bosentan, while the remaining 12 patients continued ambrisentan. Characteristics at baseline, 1-and 2-year follow-up points were compared. Results: There were no significant differences in echocardiogram, WHO-FC, hemodynamics, demographics and liver function at baseline, 1-and 2-year points in both arms. 6MWD in bosentan group was significantly shorter at baseline. But there were no significant differences of 6MWD at 1- and 2-year points. Conclusions: It is safe for stable PAH patients to transition from ambrisentan to bosentan without hemodynamic or hematologic deterioration.